A crise da racionalidade do direito brasileiro como obstáculo ao implemento das novas metas locais emancipatórias - Gerson, Fernando (Universidade do Vale do Rio dos Sinos, 2011)
The idealization of the state-reason in modernity, as theoretical justification for the preservation of the community and the achievement of common good, is strongly influenced in the belief about the legitimacy of the orders and commands laid down in law and by individuals who are appointed to exercise domination. The implementation of social welfare state is not consistent with the exercise of citizenship in liberal-individualist fragmentary and maintainer of social inequalities. The difficulties of the semi-peripheral countries such as Brazil, to conduct an effective social state of law should be reviewed from the correct insertion of the internal legal order in a complex system of economic globalization and political domination of developed countries. The imposition of an overarching rationality inherent in the international brings a metaphysical conception of universal interests, hiding the locations of the singularities appear as a way to correct the course of exploitation of national law to the true aspirations. Even in the first implementation of universal criminal jurisdiction of the history of mankind, created to protect universally recognized human rights, the ruling states have stuck to their respective sovereignty and institutionalized the selectivity of international criminal justice and the relativization of sanctions against violators of human rights. In the legal procedure, the rationalist paradigm transported from the sciences to the legal sciences guided the search for truth ontologically unattainable idealized as one of the axioms of instrumentation (inauthentic) of Brazilian law. The proposed research assumes that all knowledge is really of interest for the social and social, even if viewed from an individual perspective, because science does not cease to be a social practice, to the extent that scientific knowledge is held by an effort for understanding complex social dynamics of action of social actors in a given time and in particular social space. In this respect, to achieve the goals set by a social democratic agenda, the analysis of the factors that legitimize the right, or how to do right, becomes based on the Habermasian concept of communicative action as a step necessary for dialogic the scope of democracy material. After it is analyzed the concept of rationality of state proposed by Boaventura de Sousa Santos calls in search of local solutions, in that the more local is the social problem presented, the more local the solution should be proposed. The proposed research seeks to orient itself on the basis of epistemology critical to the understanding of the issues involving the legal rationality, the social legitimacy of law and the role of the judiciary, recognizing the local rationality and epistemic condition for achieving the targets referred to as members emancipatory for the formation of a democratic society federally.
Keywords: Racionalidade; Legitimidade social; Direito; Democracia; Rationality; Social legitimacy; Law; Democracy; ACCNPQ::Ciências Humanas::Sociologia